2018
DOI: 10.1371/journal.pone.0201305
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal analysis of canine rabies in El Salvador: Violence and poverty as social factors of canine rabies

Abstract: BackgroundThe incidence of canine rabies cases in El Salvador has decreased in the last decade since the establishment of intense control programs, such as massive vaccination campaigns implemented by the Ministry of Health. Socioeconomic crises in recent years have limited the access to certain areas across the country and have impacted surveillance and prevention campaigns, which places the country at risk for a resurgence of canine rabies.We aimedto describe the spatiotemporal patterns of canine rabies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
(36 reference statements)
2
13
0
Order By: Relevance
“…In line with previous studies (Arias-Orozco et al, 2018;Guo, Yin, et al, 2018;Hampson et al, 2015;Raghavan et al, 2016), we found that rabies distribution was negatively correlated with economic development and positively correlated with human population density. Human rabies mostly occurred in economically underdeveloped areas (RC = 6.53%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with previous studies (Arias-Orozco et al, 2018;Guo, Yin, et al, 2018;Hampson et al, 2015;Raghavan et al, 2016), we found that rabies distribution was negatively correlated with economic development and positively correlated with human population density. Human rabies mostly occurred in economically underdeveloped areas (RC = 6.53%).…”
Section: Discussionsupporting
confidence: 93%
“…Local transmission of dog rabies is also associated with dog population size and their distributions (Brunker et al., 2018; Yin et al, 2012; Zhu & Liang, 2012). Economic development is another anthropogenic factor linked to rabies transmission, with higher prevalence associated with lower economically developed areas (Arias‐Orozco et al., 2018; Hampson et al., 2015; Raghavan et al., 2016). Distance from the nearest main roads was also identified as a predictor of RABV transmission, suggesting that transport may facilitate the spread of dog rabies (Brunker et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, most of surveyed individuals were unaware of the vaccination campaign. This finding corroborates previous studies that showed the lack of awareness as a reason for low participation in canines rabies vaccination campaigns (Arias‐Orozco et al., 2018; Bardosh, 2018; Birhane et al., 2016; Castillo‐Neyra et al., 2017; Cleaton et al., 2018; Kazadi et al., 2017; Lembo et al., 2010). Indeed, better education is needed on how vaccination should be conducted every year, highlighting the importance of implementing educational programmes in vulnerable populations to increase rabies awareness and facilitate control interventions.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study show that fixed‐point vaccination methods should be a component of Haiti's vaccination campaign, but to achieve adequate herd immunity for rabies elimination additional considerations must be made. Societal changes to improve the value of dogs and dog vaccination could improve attendance, but these types of changes can take many years to develop and are often associated with improvements in the economic health of a society (Arias‐Orozco et al., 2018; Bardosh, 2018). Animal welfare changes, such as training dog owners to walk dogs on leashes or implementing laws to require dogs to remain leashed, could improve the effectiveness of fixed‐point vaccination methods.…”
Section: Discussionmentioning
confidence: 99%
“…The Stepwise Approach towards Rabies Elimination (SARE) was designed to allow rabies endemic countries to objectively measure their strengths and weaknesses, using available canine rabies evidence with scores between 0 and 5. Zero for canine rabies endemic countries and five signifying freedom from canine rabies [ [5] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ]. Several countries within the Pan-African Rabies Control Network (PARACON), such as Sierra Leone, Angola, Burkina Faso, Niger, Guinea-Bissau have a score of zero.…”
Section: Introductionmentioning
confidence: 99%